KARAKTERISASI CHRYSANTHEMUM STUNT VIROID (CSVD) YANG MENGINFEKSI KRISAN DI INDONESIA (CHRYSANTHEMUM STUNT VIROID (CSVD) CHARACTERIZE INVECTED CHRYSANTHEMUM IN INDONESIA) - TEMAJA, I G.R.M. (AGRITROP, 2010)
Chrysanthemum stunt viroid (CSVd) is an important disease of the florist’s chrysanthemum caused by viroid. The symptoms of CSVd disease were variable and are highly depend on both of cultivar and environmental conditions. The main symptom is stunting, causing the reduction of weight in overall of mature plants 30 to 50%. The other common symptoms in floral showed the infected plants having reduction of flower size and demonstrating premature flowering. CSVd is mainly transmitted by propagation, when cuttings have been taken from infected mother plants. Our survey on growing fields in Baturiti (Bali), Cipanas and Bandung (West Java), and Medan (North Sumatera) found 51.22% of samples to be infected by CSVd based on the bioassay using S. cruentus. The infections of CSVd were found in all of survey location. Using the specific primers for CSVd, a 250 bp DNA product was successfully amplified by RT-PCR technique. By sequencing analysis, Indonesian isolates were classified into two groups. The first group consist of the isolates from Cipanas, Medan and Bandung, and another group was Baturiti isolate.